Regulasi Penggunaan Teknologi Blockchain Dan Mata Uang Kripto Sebagai Tantangan Di Masa Depan Dalam Hukum Siber - Zainudin Hasan; Wiryadi Wiryadi; Arkaan Fadhulrrahman; Muhammad Dimas; Ronald Dzaky Al Jabbar (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Blockchain, originally developed as the technology behind cryptocurrencies such as Bitcoin, has gained attention for its potential to revolutionize cybersecurity. It offers a promising solution to the vulnerabilities of centralized systems by decentralizing data storage and implementing advanced encryption techniques. Blockchain technology and cryptocurrencies have presented significant challenges in the realm of cyber law to regulate them in the future, varying blockchain and crypto regulatory approaches in various countries, including regulations on crypto exchanges, ICOs, and compliance with anti- money laundering ( AML) regulations. and getting to know customers (KYC). explores the issue of data protection in blockchain transactions and i ts implications for cyber law, as well as the legality and enforcement of smart contracts. the impact of cryptocurrency use on cyber law, including challenges in tax compliance, law enforcement, and consumer protection. In the midst of various complexities regarding the direction of regulation of blockchain technology and cryptocurrencies in cyber law. with blockchain technology and cryptocurrencies and prepare views to face future challenges.